Bubbles in the Heart: A Case Series of Three Varying Presentations of Hepatopulmonary Syndrome - Anjali Jayakumar; Sibin K Prasad; Ashna Sara Mathew; Sunil Mathew; Melbin P Thankachan (Journal of Pharmacy and Bioallied Sciences)
Hepatopulmonary syndrome (HPS) is described as an arterial oxygenation deficit caused by intrapulmonary vascular dilatations in the presence of chronic liver disease. This case series highlighted three HPS cases that were brought to the emergency unit of the institution. This helps clinicians evaluate and treat hepatopulmonary syndrome and emphasizes the involvement of interprofessional teamwork. There was also hypoxemia at the time of the hospitalization, and the bubble echocardiography revealed abnormalities consistent with intrapulmonary shunting, confirming HPS. HPS is an alarming consequence of cirrhosis which leads to dyspnea in individuals. Dyspneic patients with liver illness should have a simple workup for diagnosing it.